2008
DOI: 10.1103/physrevlett.100.244504
|View full text |Cite
|
Sign up to set email alerts
|

Resonant Generation of Internal Waves on a Model Continental Slope

Abstract: We study internal wave generation in a laboratory model of oscillating tidal flow on a continental margin. Waves are found to be generated only in a near-critical region where the slope of the bottom topography matches that of internal waves. Fluid motion with a velocity an order of magnitude larger than that of the forcing occurs within a thin boundary layer above the bottom surface. The resonant wave is unstable because of strong shear; Kelvin-Helmholtz billows precede wave breaking. This work provides a new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 21 publications
3
51
0
Order By: Relevance
“…[30][31][32]34,38 Indeed, recent numerical simulations have found that turbulence generated near critical topography can reduce the radiated internal wave power. Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[30][31][32]34,38 Indeed, recent numerical simulations have found that turbulence generated near critical topography can reduce the radiated internal wave power. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Particle image velocimetry 35 has been used in laboratory studies of internal waves to characterize the velocity fields, 27,28,[36][37][38][39][40][41] and synthetic schlieren has been used in a few studies to measure density perturbations averaged along the line of sight; [42][43][44] however, measurements of the accompanying pressure fields have not been made owing to technical challenges in doing so. To circumvent the difficulty in measuring the pressure field to obtain the energy flux of two-dimensional internal waves, Echeverri et al 39 decomposed their experimental velocity fields into the three lowest vertical modes, 45 which could be used to estimate the internal wave energy flux using Eq.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of a sloping boundary, this property gives a purely geometric reason for a strong variation of the width of internal wave beams (focusing or defocusing) upon reflection. Internal wave focusing provides a necessary condition for large shear and overturning, as well as shear and bottom layer instabilities at slopes [7][8][9][10].…”
mentioning
confidence: 99%
“…One of the main reasons for studying internal waves remains the fact that they are suspected to play an important role in the dynamics of the ocean, especially in affecting the large-scale general circulation model (see e.g., [36], [49]). Furthermore, mutual interactions between internal waves produce mixing in the interior of the ocean providing an important link in the presumed energy cascade from large to small scales (e.g., [40], [47]).…”
Section: Internal Gravity Wave Beams In the Deep Oceanmentioning
confidence: 99%
“…Furthermore, mutual interactions between internal waves produce mixing in the interior of the ocean providing an important link in the presumed energy cascade from large to small scales (e.g., [40], [47]). One of the practical needs to better understand mixing processes in the ocean resides in the fact that mixing plays an important role in maintaining a gradual transition between the sun-warmed surface layer of the ocean and the upwelling cold, dense water formed at high latitudes (e.g., [49], [43], [29], [8]). The subject of mixing processes due to breaking of internal waves in the ocean and atmosphere has received much attention in recent years (see e.g.…”
Section: Internal Gravity Wave Beams In the Deep Oceanmentioning
confidence: 99%